Determination of Mesalazine Spectrophotometry Based on The Charge Transfer Complex n- π Using Reagent p-bromanil - Ghaith Al-Ramadhani; Sobhi Al-Mtioti (College of Education for Pure Sciences, 2019)
Simple, sensitive and rapid spectrophotometric method for the determination of mesalazine in pure form and pharmaceutical preparations is described. The method is based on the reaction of  mesalazine  with p-bromanil in the presence of borate buffer solution of pH9 to form a pink color charge transfer complex of maximum absorption peak (λmax) at 346 nm. Under the optimized reaction conditions, Beer's law correlating the absorbance with mesalazine  concentration was obeyed in the range of 0.48-12 μg ml-1. The molar absorptivity was 6.5×103 L.mol−1cm−1. The limits of detection was 0.053μg ml-1. The accuracy and precision of the method were satisfactory; the average recovery was 98.04% and values of relative standard deviations better than 1.70 %. The stoichiometry of the reaction was studied, and the reaction mechanism was postulated. The proposed method was successfully applied to the determination of mesalazine in its pharmaceutical tablet and capsule  with good accuracy and precisions. The results obtained by the proposed method were compared with those obtained by the official method.